Thermogravimetric analysis of giant sensitive plants under air atmosphere - Thanasit Wongsiriamnuay (2018)
The aim of this work is to utilise thermal analysis to study the thermal degradation of giant sensitive plants (Mimosa pigra L.) or Mimosa under oxidative environment. Thermogravimetric method was used under air sweeping in dynamic conditions at the heating rates of 10, 30, and 50oC/min, from room temperature to about 725oC. Starting with dehydration step between 30 and 150oC, the main thermal decomposition process under air showed two distinct degradation zones, corresponding to devolatilisation step between 200 and 375oC and combustion step around 375-500oC. Kinetic parameters in terms of apparent activation energy and pre-exponential factor were determined. Comparison was made against other biomass materials. Mass loss and mass loss rates were strongly affected by heating rate. It was found that an increase in heating rate resulted in a shift of thermograms to higher temperatures. As the heating rates increased, average devolatilisation and combustion rates were observed to increase while the activation energy showed slight increase. © 2010 Elsevier Ltd.